Routine Functional Reception Of Simaan Al-Qur’an At JHQ UIN K.H. Abdurrahman Wahid Pekalongan (Living Qur’an Study) - Sholihah, Nisaus; Azizi, Muhammad Rizki; Sya’baniyah, Nadira (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2025)
This study examines the functional reception of the tradition of routine Qur’an recitation carried out by the Jam’iyyah Hifdzil Qur’an (JHQ) community at UIN (State Islamic University of) KH. Abdurahman Wahid Pekalongan. The method used is qualitative with a sociological phenomenological approach, because this paper examines social reality as a product of intersubjectivity and how people construct meaning in their daily lives. The results of the study indicate that the routine of simaan (Qur’an recitation) functions as a means of dhikr, a medium for maintaining memorization, relieving boredom, as well as a place to strengthen brotherhood and build Qur’anic relationships. This tradition is also considered capable of creating a superior and adaptive Qur’anic generation amid the challenges of the digital era. Thus, the JHQ community plays a significant role in fostering student character based on Islamic educational principles such as monotheism, morality, knowledge, justice, and spirituality. This study contributes to the development of contemporary Living Qur’an studies in the campus environment by highlighting the practice of functional reception as a form of actualization of Qur’anic values in the academic community.